2007
DOI: 10.1111/j.1462-2920.2007.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Decline of soil microbial diversity does not influence the resistance and resilience of key soil microbial functional groups following a model disturbance

Abstract: Analysing the consequences of the decrease in biodiversity for ecosystem functioning and stability has been a major concern in ecology. However, the impact of decline in soil microbial diversity on ecosystem sustainability remains largely unknown. This has been assessed for decomposition, which is insured by a large proportion of the soil microbial community, but not for more specialized and less diverse microbial groups. We determined the impact of a decrease in soil microbial diversity on the stability (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(203 citation statements)
references
References 33 publications
10
184
3
6
Order By: Relevance
“…In contrast, this was not observed for the community structure, except for U-G treatment after 24 months. This shows that similar nitrifier activity can be insured by AOB communities differing in their community structure, which is consistent with the high functional redundancy of soil bacterial communities including nitrifiers (Wertz et al, 2006(Wertz et al, , 2007. Investigating the composition of the active nitrifier community using mRNA rather than the genetic community structure could partly explain the decoupling observed between nitrifier activity and community structure.…”
Section: G -G V S U -Usupporting
confidence: 70%
“…In contrast, this was not observed for the community structure, except for U-G treatment after 24 months. This shows that similar nitrifier activity can be insured by AOB communities differing in their community structure, which is consistent with the high functional redundancy of soil bacterial communities including nitrifiers (Wertz et al, 2006(Wertz et al, , 2007. Investigating the composition of the active nitrifier community using mRNA rather than the genetic community structure could partly explain the decoupling observed between nitrifier activity and community structure.…”
Section: G -G V S U -Usupporting
confidence: 70%
“…There is speculation that the broad taxonomic distribution of functional traits within microbial communities may confer functional robustness to losses of taxa and changes in composition (Giller et al, 1997;Wolters et al, 2000;Griffiths et al, 2001;Wertz et al, 2007). Intriguingly, this study shows that microbial community composition itself can be robust both to changing climate and to associated changes in plant production and species composition.…”
Section: Discussionmentioning
confidence: 60%
“…As the main assumption made by the neutral model is the functional equivalence of taxa (Hubbell, 2001), no compositional changes, but rapid functional adaptations of dispersed populations, should occur when they arrive in a new habitat, as functional plasticity is expected to be high. This corresponds to the adjustment scenario of Comte and del Giorgio (2011) and is supported by studies that have shown that microbial communities can functionally adapt to different environments even without drastic changes in composition, and that microbial communities of different composition can perform equally owing to their functional redundancy (Wohl et al, 2004;Wertz et al, 2007;Comte and del Giorgio, 2010;Werner et al, 2011).…”
Section: Introductionmentioning
confidence: 53%